Effect of Alumina Phase Transformation on Stability of Low-Loaded Pd-Rh Catalysts for CO Oxidation; Topics in Catalysis; Vol. 60, iss. 1 - Vedyagin A. A. Aleksey Anatolievich; Volodin A. M. Alexander; Stoyanovskii V. O. Vladimir; Kenzhin R. M. Roman; Plyusnin P. E. Pavel; Shubin Yu. V. Yury; Mishakov I. V. Iljya Vladimirovich (2017, 2017)
Title screen